2004
DOI: 10.1136/bjo.2003.019273
|View full text |Cite
|
Sign up to set email alerts
|

Case selection in macular relocation surgery for age related macular degeneration

Abstract: Background: To date there has been no randomised controlled trial demonstrating the safety and efficacy of macular relocation surgery (MRS) for age related macular degeneration (AMD). Vision can be improved in some patients and made worse in others despite successful surgery or because of complications. Purpose: To determine which patients would benefit from MRS. Methods: Twenty nine patients with exudative AMD took part in a prospective, non-comparative, interventional study. Macular relocation surgery involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 22 publications
(17 reference statements)
3
31
1
1
Order By: Relevance
“…In our series, the preoperative level of VA did not prove to be a statistically significant factor for change in VA postoperatively. Similar findings have been reported by Wong et al 19 Lesion size and lesion composition also have been proposed to impact visual outcome. At 12 months, we saw better outcome in patients with hemorrhagic AMD or classic CNV, whereas Wong et al 19 reported poorer functional outcome for patients with minimally classic CNV compared with patients with predominantly classic CNV.…”
Section: Commentsupporting
confidence: 76%
See 1 more Smart Citation
“…In our series, the preoperative level of VA did not prove to be a statistically significant factor for change in VA postoperatively. Similar findings have been reported by Wong et al 19 Lesion size and lesion composition also have been proposed to impact visual outcome. At 12 months, we saw better outcome in patients with hemorrhagic AMD or classic CNV, whereas Wong et al 19 reported poorer functional outcome for patients with minimally classic CNV compared with patients with predominantly classic CNV.…”
Section: Commentsupporting
confidence: 76%
“…Thus, case selection may be the key to predict outcome and to define the role of full macular translocation. 19 However, data on predictive factors are inconsistent. Mruthyunjaya and coworkers 15 reported that better levels of preoperative visual function were predictive of better levels 12 months after full macular translocation.…”
Section: Commentmentioning
confidence: 98%
“…Wong et al 29 have demonstrated for full macular translocation, that preoperative VA (20/120 or better) and lesion type (predominantly classic or submacular haemorrhage) is predictive for visual improvement. This is in accordance to our results indicating that patients benefit the most when the duration of the disease is shortest (probably in patients with classic or predominantly classic lesions and submacular haemorrhage).…”
Section: Recommendations For Case Selection For Patch Translocationmentioning
confidence: 99%
“…[7][8][9] Complication related to FMT included retinal detachment, macular oedema, persistent hypotony, and disturbing diplopia. [7][8][9] Our results showed a slightly more favourable visual outcome for patients receiving more than one PDT session before the FMT, differing from the results of Park and Toth. 5 However, the small sample size analysed in both studies makes a reasonable statement difficult.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] The purpose of this retrospective case study is to elucidate the long-term functional and morphological outcome of PDT-nonresponders who had undergone FMT in neovascular AMD.…”
Section: Introductionmentioning
confidence: 99%